Outcomes and costs of treating hepatitis C patients with second-generation direct-acting antivirals: results from the German Hepatitis C-Registry. Issue 2 (February 2019) - Krüger, Kathrin; Krauth, Christian; Rossol, Siegbert; Mauss, Stefan; Boeker, Klaus H.W.; Müller, Tobias; Klinker, Hartwig; Pathil, Anita; Heyne, Renate; Stahmeyer, Jona T.
Abstract : Objective: Chronic hepatitis C virus infection is associated with a significant health burden. Long-term consequences are the development of liver cirrhosis and hepatocellular carcinoma. The introduction of direct-acting antivirals (DAA) has led to an increase in sustained virologic response rates (SVR), but is accompanied by higher treatment costs. The aim of this study was to assess the outcomes and costs of treating hepatitis C virus infected patients with DAAs in clinical practice in Germany. Patients and methods: Data were derived from a noninterventional study including a pharmacoeconomic subset of 2673 patients with genotypes 1 and 3 who initiated and completed treatment between February 2014 and February 2017. Sociodemographic and clinical parameters as well as resource utilization were collected using a web-based data recording system. Costs were calculated using official remuneration schemes. Results: The mean age of the patients was 54.6 years; 48% were men. 93.5% of all patients achieved an SVR. The average total treatment costs were [Euro sign]67 979 ([Euro sign]67 131 medication costs, [Euro sign]824 ambulatory care, [Euro sign]24 hospital costs). The average costs per SVR of [Euro sign]72 705 were calculated. Differences in SVR and costs according to genotype, treatment regimen, treatment experience, and cirrhosis were observed. Quality-of-life data showed no or a minimal decrease during treatment. Conclusion: This analysis confirms high SVR rates for newly introduced DAAs in a real-world setting. Costs per SVR estimated are comparable to first-generation DAA. Given the fact that the costs for the currently used treatment regimens have declined, it can be assumed that the costs per SVR have also decreased. Our insight into real-world outcomes and costs can serve as a basis for a comparison with the mentioned newly introduced treatment regimens.